Modified regenerated polyphenyl plastic material and preparation method thereof

By using specific organic compounds and nanotitanium dioxide in recycled polystyrene plastics, the problem of insufficient toughness and heat resistance of materials is solved, the performance is synergistically improved, the needs of high-end applications are met, and environmental pollution and resource waste are reduced.

CN119119647APending Publication Date: 2024-12-13HUNAN ZHONGKE NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411620019.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing recycled polyphenyl plastics have problems such as insufficient toughness, low strength and poor heat resistance in terms of performance, which limits their use in high-end applications, and their wastes pollute the environment and wastes serious resources.

Method used

Organic compounds such as 2,4-dihydroxybenzoic acid-3-butenyl ether ester and 4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamide ethyl ester are used as toughening agents and reinforcement agents , combined with nanotitanium dioxide as a reinforced filler, the toughness and strength of the material are significantly improved through hydrogen bonding and chemical reactions, and the uniform dispersion and molding effect of each component is ensured by optimizing process parameters.

Benefits of technology

It significantly improves the toughness, strength and heat resistance of recycled polystyrene plastics, meets a wider application demand, reduces resource waste and environmental pollution, reduces production costs, and expands its application possibilities in high-end fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of materials, in particular to a modified regenerated polyphenyl plastic material and a preparation method thereof, and the modified regenerated polyphenyl plastic material is prepared from the following components: 60 to 100 parts of waste polyphenyl plastic particles, 2 to 6 parts of 2, 4-dihydroxybenzoic acid-3-butenyl ether ester, 1 to 4 parts of 4-amino-3, 5-dimethyl benzenesulfonic acid-2-acrylamide ethyl ester, 2 to 6 parts of nano titanium dioxide and 0.1 to 0.5 part of antioxidant. A novel organic compound is adopted as a toughening agent and a reinforcing agent, and the toughening agent and the reinforcing agent have unique molecular structures, so that the toughness and the strength of the regenerated polyphenyl plastic can be remarkably improved through hydrogen-bond interaction and chemical reaction respectively, meanwhile, the heat resistance and the chemical stability are improved, and the limitation of a traditional modifier is overcome; compared with a traditional regenerated polyphenyl plastic material, the regenerated polyphenyl plastic material has obvious advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building wall materials, and in particular to a modified recycled polystyrene plastic material and a preparation method thereof. Background Art

[0002] In today's society, plastic products have been widely used in various fields due to their excellent performance and wide applicability. However, with the large-scale production and consumption of polystyrene plastic products, the amount of waste is also increasing day by day, bringing tremendous pressure to the environment.

[0003] On the one hand, if a large amount of discarded polystyrene plastics are not properly handled, they will cause serious pollution to the environment. Polystyrene plastics are difficult to degrade in the natural environment, and their waste will remain in the soil for a long time, destroying the soil structure, affecting the air permeability and water penetration capacity of the soil, and then hindering the growth of plant roots and the absorption of nutrients, and having a negative impact on agricultural production and ecological balance. In the aquatic environment, discarded polystyrene plastics will float on the water surface or settle on the bottom of the water, which not only affects the beauty of the water body and the normal circulation of the ecosystem, but may also be accidentally eaten by aquatic organisms, causing blockage of their digestive system or even death, seriously threatening the survival and reproduction of aquatic organisms and destroying the balance of the aquatic ecosystem. In addition, when discarded polystyrene plastics are incinerated, they will also release a large amount of harmful gases, such as dioxins, which pollute the atmospheric environment and endanger human health.

[0004] On the other hand, from the perspective of resource utilization, polystyrene plastics are made from valuable non-renewable resources such as petroleum, and large amounts of waste means a huge waste of resources. As global resources become increasingly scarce, it is essential to improve the recycling rate of resources. The emergence of recycled polystyrene plastics provides a way to solve this problem, but at present, recycled polystyrene plastics still have many shortcomings in terms of performance, which limits their further application and development.

[0005] Recycled polystyrene plastics often have the problem of insufficient toughness, which makes them easy to break when subjected to external impact. This is particularly evident in some application scenarios that require high material toughness, such as packaging materials need to withstand collisions during transportation, and building materials need to cope with certain external force deformation. Low strength is also a shortcoming of recycled polystyrene plastics. Its mechanical properties such as tensile strength and bending strength are difficult to meet the requirements of some high-end application fields, affecting the product's reliability and life. In addition, poor heat resistance makes recycled polystyrene plastics easy to deform and soften in high temperature environments, limiting its application under high temperature working conditions. For example, in some electronic and electrical equipment, plastic materials need to have certain heat resistance to ensure the normal operation of the equipment.

[0006] In summary, in order to reduce the pollution of waste polystyrene plastics to the environment, realize the effective recycling of resources, and meet the growing market demand for high-performance plastic materials, modifying recycled polystyrene plastics to improve their comprehensive performance has become a key issue to be solved in the field of plastic materials. Therefore, the present invention aims to develop a modified recycled polystyrene plastic material with superior performance through innovative material component design and optimized preparation process to overcome the defects of the prior art. Summary of the invention

[0007] The invention provides a novel high-performance recycled polystyrene plastic building wall material and a preparation method thereof. The material comprises the following components in mass ratio: 35-45 parts of waste polystyrene plastic particles, 3.5-6 parts of 2-hydroxy-3-carboxybenzoic acid ethyl ester propyl ether, 2-4 parts of 4-amino-5-phosphate ester-2-phenylpyridine, and 1-12 parts of glass fiber, or comprises the following components: 60-100 parts of waste polystyrene plastic particles, 2-6 parts of 2,4-dihydroxybenzoic acid-3-butylene ether ester, 1-4 parts of 4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamidoethyl ester, 2-6 parts of nano titanium dioxide, 0.1-0.5 parts of antioxidant, and 0.3-0.8 parts of lubricant.

[0008] Furthermore, the toughening agent is 2,4-dihydroxybenzoic acid-3-butenyl ether ester. The hydroxyl group in the organic compound forms hydrogen bonds with the surface of the recycled polystyrene plastic particles to enhance the interfacial affinity. The butenyl ether ester group has good flexibility and elasticity and can significantly improve the toughness of the recycled polystyrene plastic.

[0009] Furthermore, the reinforcing agent is 1-4 parts, and its chemical name is 4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamide ethyl ester. The amino group can react chemically with the recycled polystyrene plastic particles to form a covalent bond and enhance the interfacial bonding force. The acrylamide ethyl group can form a cross-linked network structure in the material to improve the strength and rigidity of the material. The benzenesulfonic acid group can improve the heat resistance and chemical stability of the material.

[0010] Furthermore, the method for preparing the modified recycled polystyrene plastic material comprises the following steps: Step 1: Raw material pretreatment, classify the recycled waste polystyrene plastics, remove impurities, clean them with a cleaning agent, remove dirt and attachments on the surface, and crush the cleaned polystyrene plastics for later use; dry the nano titanium dioxide in a drying oven to remove moisture adsorbed on its surface and improve its compatibility with the polymer matrix; Step 2: Synthesis of organic compound A: In a reaction kettle, raw materials and catalyst triethylamine are added in a ratio of 2,4-dihydroxybenzoic acid: 3-butenyl chloroformate of 1:1.2, and the temperature is raised to 60 degrees Celsius under nitrogen protection to carry out esterification reaction, and unreacted raw materials and by-products are removed by reduced pressure distillation, and then recrystallized with ethanol to obtain pure 2,4-dihydroxybenzoic acid-3-butenyl ether ester (organic compound A); Synthesis of organic compound B: In another reaction device, 4-amino-3,5-dimethylbenzenesulfonic acid and 2-acryloylethyl chloride are mixed in a solvent of dichloromethane, and an acid-binding agent, sodium carbonate, is added to carry out an acylation reaction under ice bath conditions. After the reaction is completed, 4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamidoethyl ester (organic compound B) is obtained by filtering, washing, drying and other processes; The synthesized organic compounds A and B are mixed in a mass ratio of 2:1, and an appropriate amount of dispersant is added, and stirred in a high-speed stirrer to form an organic compound mixed solution for standby use; Step 3: material mixing and molding, the pretreated recycled polystyrene plastic particles, antioxidant, lubricant and nano titanium dioxide are added to a high-speed mixer and mixed evenly, and then the organic compound mixed solution prepared in step 2 is slowly added to the high-speed mixer and mixed evenly, and the mixed materials are added to a twin-screw extruder for extrusion molding. The extruded materials are cooled and pelletized to obtain modified recycled polystyrene plastic material particles.

[0011] Furthermore, in the organic compound A, the molar ratio of 2,4-dihydroxybenzoic acid to 3-butenyl chloroformate is adjusted between 1:1 and 1:1.5 to adapt to different reaction conditions and product requirements for toughness.

[0012] Furthermore, in the synthesis of the organic compound B, the amount of the acid-binding agent sodium carbonate varies between 1 and 1.5 times the mass of 4-amino-3,5-dimethylbenzenesulfonic acid to control the progress of the acylation reaction and the quality of the product.

[0013] Furthermore, the amount of the lubricant calcium stearate varies between 0.3% and 1% of the mass of the recycled polystyrene plastic particles to adapt to different processing techniques and equipment requirements, ensure good fluidity and formability of the material during processing, and avoid negative effects of excessive lubricant on material properties.

[0014] Furthermore, the synthesis reaction temperature of the organic compound A in step 2 can vary between 55-70 degrees Celsius, and the reaction time can be adjusted between 6-10 hours. According to the activity of the raw materials and the performance of the reaction equipment, the reaction conditions are optimized to improve the reaction efficiency and product purity.

[0015] Furthermore, when the materials are mixed in step three, the mixing temperature of the high-speed mixer can be selected between 90-110 degrees Celsius, the stirring speed can be adjusted between 500-800 rpm, and the mixing time can vary between 25-35 minutes. According to the characteristics of the materials and the performance of the equipment, the mixing process parameters are optimized to ensure that the components are fully mixed.

[0016] Furthermore, the screw speed of the extruder can be adjusted between 160-220 rpm, and the extrusion temperature from the feed port to the die can be changed in sequence between 160-180 degrees Celsius, 180-200 degrees Celsius, 200-220 degrees Celsius, 220-240 degrees Celsius, and 200-220 degrees Celsius. According to the melt viscosity and molding requirements of the material, the extruder parameters are reasonably adjusted to ensure the extrusion molding quality and production efficiency of the material.

[0017] Beneficial technical effects of the invention: Organic compounds are used as tougheners and reinforcing agents. They have unique molecular structures and can significantly improve the toughness and strength of recycled polystyrene plastics through hydrogen bonding and chemical reactions, while improving heat resistance and chemical stability, overcoming the limitations of traditional modifiers. The use of nano-titanium dioxide as a reinforcing filler not only improves the mechanical properties of the material, but also improves weather resistance by virtue of its UV shielding performance, and improves rheological and processing properties by using the nano-size effect, opening up a new way to improve material performance. The synthesis process of organic compounds is precisely controlled, including the molar ratio of raw materials, reaction temperature, time, selection and dosage of catalysts and acid-binding agents, to ensure the high purity and performance stability of the compounds, laying the foundation for the high performance of subsequent materials. In the material mixing stage, by strictly controlling the order of addition of each component, mixing temperature, stirring speed and time, as well as the screw speed and temperature distribution of the extruder, the uniform dispersion of each component and good molding effect are achieved, ensuring the stability and consistency of product quality. By recycling and reusing waste polystyrene plastics, resource waste and environmental pollution are reduced, which is in line with the concept of sustainable development, reduces production costs, and provides an effective solution for the treatment of waste plastics. The successful synergistic improvement of the strength, toughness, heat resistance and weather resistance of recycled polystyrene plastics has been achieved, enabling it to meet a wider range of application needs, breaking through the bottleneck of traditional recycled polystyrene plastics with single performance or poor overall performance, and expanding its application possibilities in high-end fields. DETAILED DESCRIPTION

[0018] Example 1 The composition of modified recycled polystyrene plastic materials: recycled polystyrene plastic particles are obtained through pre-treatment processes such as screening, cleaning, and crushing, and the particle size is controlled at 1-3mm. By recycling and reusing waste polystyrene plastics, resource waste and environmental pollution are reduced, while production costs are reduced.

[0019] Chemical name of organic compound A (toughening agent): 2,4-dihydroxybenzoic acid-3-butenyl ether ester, structural formula: a hydroxyl group is connected to the 2nd and 4th positions of the benzene ring, the benzene ring is connected to an oxygen atom through a carbonyl group, and the oxygen atom is connected to a butenyl ether ester group, design principle: the hydroxyl group in the organic compound can form hydrogen bonds with the surface of the recycled polystyrene plastic particles to enhance the interface affinity. The butenyl ether ester group has good flexibility and elasticity, and can significantly improve the toughness of recycled polystyrene plastics. Its unique molecular structure can play a dual role of plasticization and toughening in the polystyrene plastic matrix, so that the material can better absorb energy when subjected to external forces and reduce the generation and expansion of cracks.

[0020] Organic compound B (enhancer) Chemical name: 4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamide ethyl ester Structural formula: An amino group is connected to the 4th position of the benzene ring, and a methyl group is connected to the 3rd and 5th positions respectively. The benzene ring is connected to an oxygen atom through a sulfonic acid group, and the oxygen atom is connected to an acrylamide ethyl ester group. Design principle: The amino group can react chemically with the recycled polystyrene plastic particles to form a covalent bond and enhance the interfacial bonding force. The acrylamide ethyl ester group can form a cross-linked network structure in the material to improve the strength and rigidity of the material. At the same time, the presence of the benzenesulfonic acid group can improve the heat resistance and chemical stability of the material. The introduction of this organic compound can significantly improve the comprehensive performance of recycled polystyrene plastic materials without significantly increasing the cost.

[0021] Nano-reinforced filler: Nano titanium dioxide is selected, and its particle size is 30-60nm. Nano titanium dioxide has high strength and hardness, and can effectively improve the mechanical properties of the material. It also has good ultraviolet shielding properties, which can improve the weather resistance of the material. At the same time, the nano-size effect can also improve the rheological properties and processing properties of the material. The antioxidant uses a hindered phenol antioxidant, such as antioxidant 1010. The function of the antioxidant is to prevent the oxidation degradation of recycled polystyrene plastics during processing and use, and improve the stability and service life of the material. It can capture free radicals and interrupt the oxidation chain reaction, thereby protecting the polymer molecular chain from being destroyed. Lubricant Calcium stearate is selected as a lubricant. The addition of lubricant can reduce the friction of the material during processing, improve the fluidity of the melt, make the material easier to shape and process, and at the same time reduce the wear of the equipment and improve production efficiency.

[0022] Preparation method, step 1: raw material pretreatment. The recycled polystyrene plastic is classified to remove impurities, and then cleaned with a cleaning agent to remove surface dirt and attachments. The cleaned polystyrene plastic is crushed into particles with a particle size of 1-3 mm in a pulverizer for standby use. The nano-titanium dioxide is dried in a drying oven, the temperature is set to 150 degrees Celsius, and the drying time is 6 hours to remove the moisture adsorbed on its surface and improve the compatibility with the polymer matrix. Step 2: Synthesis and treatment of organic compounds: Synthesis of organic compound A: In a reactor, raw materials and catalysts (triethylamine is used as the catalyst, and the amount is 5% of the mass of 2,4-dihydroxybenzoic acid) are added according to a certain molar ratio (such as 2,4-dihydroxybenzoic acid: 3-butenyl chloroformate = 1:1.2). Under nitrogen protection, the temperature is raised to 60 degrees Celsius for esterification reaction, and the reaction time is 8 hours. After the reaction is completed, unreacted raw materials and by-products are removed by reduced pressure distillation, and then recrystallization is performed with ethanol to obtain pure 2,4-dihydroxybenzoic acid-3-butenyl ether ester (organic compound A). .

[0023] Synthesis of organic compound B: In another reaction device, 4-amino-3,5-dimethylbenzenesulfonic acid and 2-acryloylethyl chloride are mixed in a solvent (dichloromethane is used as the solvent, and the amount used is 40% of the total mass of the raw materials), and an acid binding agent is added (sodium carbonate is used as the acid binding agent, and the amount used is 1.2 times the mass of 4-amino-3,5-dimethylbenzenesulfonic acid). Acylation reaction is carried out under ice bath conditions (temperature is controlled at 0-5 degrees Celsius), and the reaction time is 10 hours. After the reaction is completed, 4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamidoethyl ester (organic compound B) is obtained by filtering, washing, drying and other processes.

[0024] .

[0025] The synthesized organic compounds A and B are mixed in a mass ratio of 2:1, and an appropriate amount of dispersant (polyvinyl pyrrolidone is selected as the dispersant, and the amount is 4% of the total mass of the organic compound) is added, and stirred at a speed of 1200 rpm in a high-speed mixer for 20 minutes to form an organic compound mixed solution for standby use. Step 3: Material mixing and molding: The pretreated recycled polystyrene plastic particles, antioxidant (the amount of antioxidant 1010 is 0.3% of the mass of the recycled polystyrene plastic particles), lubricant (the amount of calcium stearate is 0.6% of the mass of the recycled polystyrene plastic particles) and nano titanium dioxide (the amount of nano titanium dioxide is 4% of the mass of the recycled polystyrene plastic particles) are added to the high-speed mixer. Mix for 30 minutes at a temperature of 100 degrees Celsius and a stirring speed of 600 rpm to fully mix the components. Then slowly add the organic compound mixed solution prepared in step 2 to the high-speed mixer, and continue stirring for 30 minutes to fully mix the components. Add the mixed materials to a twin-screw extruder for extrusion molding. The screw speed of the extruder is 180 rpm, and the extrusion temperature from the feed port to the die head is set to 170 degrees Celsius, 190 degrees Celsius, 210 degrees Celsius, 230 degrees Celsius, and 210 degrees Celsius. The extruded material is cooled and pelletized to obtain modified recycled polystyrene plastic material particles.

[0026] Example 2 The purpose is to further illustrate the feasibility and effectiveness of the modified recycled polystyrene plastic material and the preparation method thereof of the present invention, and to demonstrate its advantages through comparative experiments.

[0027] Raw material preparation, recycled polystyrene plastic particles: collect discarded polystyrene plastic products, wash and crush them to obtain particles with a particle size of 1-2mm, prepare 100kg. Organic compound A (2,4-dihydroxybenzoic acid-3-butenyl ether ester): prepared according to the above synthesis method, obtain 4kg. Organic compound B (4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamidoethyl ester): obtained after synthesis 2kg. Nano titanium dioxide: particle size is 30-50nm, prepare 4kg. Antioxidant 1010: 0.3kg. Calcium stearate: 0.6kg.

[0028] Preparation process: Raw material pretreatment: wash and crush the polystyrene plastic particles to the required particle size, and dry the nano-titanium dioxide. Synthesis and treatment of organic compounds: prepare organic compounds A and B respectively according to the synthesis process, and mix them evenly to form a solution. Material mixing and molding: add recycled polystyrene plastic particles, antioxidants, lubricants and nano-titanium dioxide to a high-speed mixer and mix them evenly, then slowly add the organic compound mixed solution, continue to stir evenly, and extrude it through a twin-screw extruder.

[0029] Performance test and comparative test, mechanical property test: the prepared material was subjected to tensile and bending tests using a universal material testing machine. The results showed that the tensile strength reached 29MPa, the elongation at break was 45%, and the bending strength was 36MPa. Comparative test: A common prior art modified recycled polystyrene plastic product A on the market (which uses traditional tougheners and reinforcing agents, specifically commercially available elastomer tougheners and glass fiber reinforcing agents) was selected for the same mechanical property test. The results showed that the tensile strength of product A was 23MPa, the elongation at break was 30%, and the bending strength was 30MPa. The material of the present invention is significantly superior to product A in terms of strength and toughness. Another prior art product C (using different chemical modification methods and additive combinations) was selected, with a tensile strength of 24MPa, an elongation at break of 32%, and a bending strength of 31MPa. Compared with product C, the material of the present invention also exhibits better mechanical properties.

[0030] Heat resistance test, tested by heat deformation temperature tester, the heat deformation temperature of the material of the present invention is 88 degrees Celsius. Comparative test: The heat deformation temperature of product B (whose formula and process are different from those of the present invention) is 75 degrees Celsius. The heat deformation temperature of product C is 78 degrees Celsius. The heat resistance of the material of the present invention is higher than that of product B and product C. Weather resistance test: The material sample is placed in a UV aging test box and an accelerated aging test is carried out for 1000 hours. After the test, the color change of the material of the present invention is small, and the mechanical property retention rate is high (tensile strength retention rate is 85%, and elongation at break retention rate is 80%). Comparative test: The same weather resistance test is carried out on prior art products A and B. The tensile strength retention rate of product A is 65%, and the elongation at break retention rate is 55%; the tensile strength retention rate of product B is 70%, and the elongation at break retention rate is 60%. The tensile strength retention rate of product C is 72%, and the elongation at break retention rate is 63%. The material of the present invention performs better in weather resistance.

[0031] Example 3 Raw material preparation and process parameter adjustment, recycled polystyrene plastic particles: particle size is 2-3mm, prepare 120kg. Organic compound A (2,4-dihydroxybenzoic acid-3-butenyl ether ester): 5kg is obtained after synthesis. Organic compound B (4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamidoethyl ester): 3kg. Nano titanium dioxide: particle size is 40-60nm, prepare 5kg. Antioxidant 1010: 0.36kg. Calcium stearate: 0.72kg. During the raw material pretreatment process, the recycled polystyrene plastic particles are screened more finely to remove smaller impurities, and the surface is activated (using plasma treatment technology, the treatment time is 5 minutes, the power is 100W) to further improve the bonding with other components. In the process of synthesizing organic compounds, the synthesis reaction temperature of organic compound A was adjusted to 65 degrees Celsius and the reaction time was 9 hours; in the synthesis of organic compound B, the dripping speed of 2-acryloyl ethyl chloride was slowed down (the dripping time was extended to 2 hours) to improve the uniformity and yield of the reaction. In the process of mixing materials, the mixing temperature was adjusted to 105 degrees Celsius, the stirring speed was 800 rpm, and the mixing time was 35 minutes (before adding the organic compound solution) and 35 minutes (after adding the organic compound solution). The screw speed of the extruder was adjusted to 200 rpm, and the extrusion temperature was set to 175 degrees Celsius, 195 degrees Celsius, 215 degrees Celsius, 235 degrees Celsius, and 215 degrees Celsius from the feed port to the die head.

[0032] Performance test and result analysis and comparison, mechanical properties test results: tensile strength reaches 32MPa, elongation at break is 50%, and bending strength is 39MPa. Comparative test: Product A, product B and product C are selected again for comparative testing. The tensile strength of product A is still about 23MPa, and the elongation at break and bending strength do not change much; the tensile strength of product B is 25MPa, the elongation at break is 35%, and the bending strength is 33MPa; the tensile strength of product C is 26MPa, the elongation at break is 38%, and the bending strength is 35MPa. The mechanical properties of the material of Example 2 of the present invention are further improved, and the advantages are more obvious. Heat resistance test: The heat deformation temperature is 92 degrees Celsius. Compared with product B (heat deformation temperature of 75 degrees Celsius) and product C (heat deformation temperature of 78 degrees Celsius), the heat resistance gap is further widened, and the heat resistance of the material of the present invention is better improved. Weathering test: After 1000 hours of UV aging test, the color change of the material of the present invention is smaller, and the mechanical property retention rate is higher (tensile strength retention rate is 88%, and elongation at break retention rate is 83%). However, the mechanical property retention rates of product A (tensile strength retention rate is 65%, and elongation at break retention rate is 55%), product B (tensile strength retention rate is 70%, and elongation at break retention rate is 60%), and product C (tensile strength retention rate is 75%, and elongation at break retention rate is 65%) are still lower than those of the material of the present invention, which further proves the superiority of the material of the present invention in terms of weathering resistance.

Claims

1. A modified recycled polystyrene plastic material, characterized in that: The invention comprises the following components in mass ratio: waste polystyrene plastic particles: 60-100 parts, 2,4-dihydroxybenzoic acid-3-butenyl ether ester: 2-6 parts, 4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamidoethyl ester: 1-4 parts, nano titanium dioxide: 2-6 parts, hindered phenol antioxidant 1010: 0.1-0.5 parts, and lubricant calcium stearate: 0.3-0.8 parts.

2. The method for preparing the modified recycled polystyrene plastic material according to claim 1, characterized in that: The following steps are involved: Step 1: Raw material pretreatment, classify the recycled waste polystyrene plastic, remove impurities, and crush for standby use; dry the nano titanium dioxide in a drying oven; Step 2: In a reaction kettle, 2,4-dihydroxybenzoic acid and 3-butenyl chloroformate are added with a catalyst triethylamine to carry out an esterification reaction, and then recrystallized with ethanol to obtain a pure 2,4-dihydroxybenzoic acid-3-butenyl ether ester organic compound A; In another reaction device, 4-amino-3,5-dimethylbenzenesulfonic acid and 2-acryloylethyl chloride are mixed in a solvent of dichloromethane, and an acid-binding agent, sodium carbonate, is added to carry out an acylation reaction. After the reaction is completed, 4-amino-3,5-dimethylbenzenesulfonic acid-2-acrylamidoethyl ester organic compound B is obtained by filtering, washing, and drying processes; The synthesized organic compounds A and B are mixed in a mass ratio of 2:1, and a dispersant is added, and stirred in a high-speed stirrer to form an organic compound mixed solution for later use; Step 3: Material mixing and molding, the pretreated waste polystyrene plastic, antioxidant, lubricant and nano titanium dioxide are added to a high-speed mixer and mixed evenly, then the organic compound mixed solution prepared in step 2 is slowly added to the high-speed mixer, mixed evenly, and the mixed material is added to a twin-screw extruder for extrusion molding. The extruded material is cooled and pelletized to obtain modified recycled polystyrene plastic material particles.

3. The method for preparing modified recycled polystyrene plastic material according to claim 2, characterized in that: In the synthesis of the organic compound B, the amount of the acid-binding agent sodium carbonate is 1 to 1.5 times the mass of 4-amino-3,5-dimethylbenzenesulfonic acid.

4. The method for preparing modified recycled polystyrene plastic material according to claim 2, characterized in that: The amount of the lubricant calcium stearate is 0.3%-1% of the mass of the recycled polystyrene plastic particles.

5. The method for preparing modified recycled polystyrene plastic material according to claim 2, characterized in that: The synthesis reaction temperature of the organic compound A in step 2 is 55-70 degrees Celsius, and the reaction time is 6-10 hours.

6. The method for preparing modified recycled polystyrene plastic material according to claim 2, characterized in that: When the materials are mixed in step 3, the mixing temperature of the high-speed mixer is 90-110 degrees Celsius, the stirring speed is 500-800 rpm, and the mixing time is 25-35 minutes.

Citation Information

Patent Citations

  • Method for recycling polystyrene shell materials of waste electrical appliances

    CN102719030A

  • Renewable HIPS (high impact polystyrene) flame retardant modified material and preparation method thereof

    CN104387685A

  • Low-temperature-resistant modified polystyrene (PS) plastic particles and preparation method thereof

    CN110144089A

  • High-gloss high-flowability regenerated polystyrene material and preparation method thereof

    CN118271754A